Historical dictionary of the International Monetary Fund - Tenney, Sarah, 1960- (Historical dictionaries of international organizations series., 2011)
In its more than 65 years of existence, the International Monetary Fund has evolved from a small, obscure international agency, with new and uncertain responsibilities, into a powerful institution that today has assumed center stage in the international monetary system. It is a remarkable story of how an institution has developed and adapted itself to an evolving world and a changing membership in ways that perhaps no other international agency has been forced or able to do. The third edition of the Historical Dictionary of the International Monetary Fund provides a comprehensive overview of.